(untitled) (Andamios, Revista de Investigación Social, 2013)
The present article intends to show some of the essential features of the category of ‘critique’ in the work of K. Marx, simultaneously placing it in a conception of the critical task that started with Hegel and has continued to the present day. This conception rests on the central idea that everything substantial, both in the objects of the theory as in the categories this theory uses, has its foundation in the FORM reached historically through social relations and concepts. The ‘critique’ is simultaneously radical and also production of new knowledge. Marx´s epistemology revolves around these ideas.